The Safe Path at the Fork: Ensuring Replication-Associated DNA Double-Strand Breaks are Repaired by Homologous Recombination - Nickoloff, Jac A.; Sharma, Neelam; Taylor, Lynn; Allen, Sage J.; Hromas, Robert (Frontiers in Genetics, 2021)
Dividing cells must replicate and segregate their DNA to daughter cells with sufficient accuracy to maintain genome stability and prevent cancer. DNA replication is normally fast and accurate, with intrinsic and extrinsic error-correction systems. However, replication is not a smooth, continuous process, but is rather choppy because replication forks slow or stop when they encounter DNA lesions, natural pause sites, and difficult-to-replicate sequences. Replication is also slowed or stopped by DNA polymerase inhibitors and nucleotide pool depletion by hydroxyurea. These challenges are termed replication stress, to which cells respond by activating DNA damage response signaling pathways that arrest the cell cycle, stimulate DNA repair and replication fork restart, or induce apoptosis. Mechanisms to repair and restart stressed replication forks include rescue by an adjacent fork, repriming, translesion synthesis, template switching, and fork reversal which produces a one-ended double-strand break (DSB). Replication forks also collapse to one-ended DSBs when they encounter a single-strand nick or stalled forks are cleaved by MUS81-EME2 or EEPD1. Reversed and cleaved forks can be restarted by homologous recombination (HR), but the one-ended DSB intermediates pose significant risk of mis-rejoining by non-homologous end-joining (NHEJ) with other broken forks or other DSBs, causing genome rearrangements. HR requires resection of broken ends to create 3’ single-stranded DNA for RAD51 recombinase loading, and resected ends are refractory to repair by NHEJ. This Mini Review highlights mechanisms that help maintain genome stability by promoting resection of one-ended DSBs at broken replication forks to promote accurate fork restart by HR.